Effectiveness of Cognitive Function and Activity of Daily Living (ADL) on Elderly Independence - Andre Utama Saputra; Nila Alfa Fauziah; Jupiter Eko Saputra (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Aging is a natural process followed by physical and behavioural changes. All individuals will experience the process of growing old and old age is the final stage of human life, where there is a gradual physical, mental and social decline. Actual deterioration occurs in the elderly will reduce muscle mass and flexibility, so it can affect the capacity of the elderly to meet their needs. The lack of elderly activities carried out independently in daily activities, elderly people aged 85 years and over have difficulty in managing daily activities, and deterioration of cognitive function. Objective: To determine the Effectiveness of Cognitive Function and Activity of Daily Living (ADL) on Elderly Independence at Panti Sosial Harapan Kita Palembang. Methods: This study used parametric statistics to determine the relationship between cognitive function and Activity Of Daily Living on independence with a sample of 36 respondents taken by total sampling technique. Results: The results of the statistical test obtained a p value of 0.766 means that there is no significant relationship between cognitive function and independence. As for the relationship between Activity of daily living and the independence of the elderly, the p value is 0.039, meaning that there is a significant relationship between Activity of Daily Living and independence. Conclusion: There is no significant relationship between cognitive function and independence and there is a significant relationship between Activity of Daily Living and the independence of the elderly at Harapan Kita Palembang social centre.